Unlocking E-Government Success: Key Factors Driving E-Absence Adoption in Public Sector - Afrizal, Dedy; Erlianti, Dila; Hijeriah, E. Maznah; Hafrida, Lis; Erinaldi, Erinaldi; Luthfi, Ahmad (Departemen Ilmu Administrasi FISIP UNHAS, 2024)
The use of e-absence for government servants is currently an innovative way to improve the efficiency of work activities in local government. The focus on how the system is implemented and used by government servants is also important to discuss. The research aims to explore how government servants intend to use the e-absence application provided by the Dumai city government. The unified theory of acceptance and use of technology (UTAUT) model is used for examining research problems in which the model has been modified to include a new variable, attitude. This study used a quantitative approach and quota sampling technique that included 100 respondents, all of whom were government servants working for different Dumai government agencies. Questionnaires were distributed using Google forms, with questions adapted from previous research. The study showed that performance expectancy, social influence, and attitude are all significantly and positively connected to intention to use e-absence dan effort expectation and social impact are not significantly and negatively to the intention to use e-absence. Several recommendations for theoretical advancement and the development of the e-attendance system itself have been provided.